Hydrodynamics of liquid-liquid dispersion in an advanced-flow reactor - Nieves-Remacha, Maria Jose; Kulkarni, Amol A.; Jensen, Klavs F. (Industrial & Engineering Chemistry Research, 2012)
Hydrodynamics and mass transfer of immiscible liquid-liquid flows are explored in an Advanced-Flow Reactor (AFR). These systems are emerging as one of the major commercial systems for small scale continuous flow chemistry, and characterization of the transport phenomena is critical for reaction implementation. With hexane/water as a model system, we use flow visualization techniques to determine drop size distribution, hexane holdup, and specific interfacial areas for a phase flow rate range of 10-80 mL/min. The complex geometry of the AFR with its continuously changing cross section along the flow path and strategically placed obstacles creates pressure changes that cause drop breakup and enhance mass transfer. Observations show that a wide range of average drop size (0.33-1.3 mm) can be achieved in the AFR depending upon the inlet flow rates and inlet composition. Pressure drop measurements are performed to estimate the power consumption and are used to compare the efficiency of AFR with conventional liquid-liquid contactors. The analysis shows that, similar to microreactors, the AFR can provide specific interfacial areas (1000-10 000 m(-1)) and overall mass transfer coefficients (1.9-41 s(-1)) a few orders of magnitude larger than conventional stirred tank reactors and also the static mixers.

Size-controlled flow synthesis of gold nanoparticles using a segmented flow microfluidic platform - Cabeza, Victor Sebastian; Kuhn, Simon; Kulkarni, Amol A.; Jensen, Klavs F. (Langmuir, 2012)
Segmented flow is often used in the synthesis of nanomaterials to achieve narrow particle size distribution. The narrowness of the distribution is commonly attributed to the reduced dispersion associated with segmented flows. On the basis of the analysis of flow fields and the resulting particle size distribution, we demonstrate that it is the slip velocity between the two fluids and internal mixing in the continuous-phase slugs that govern the nature of the particle size distribution. The reduction in the axial dispersion has less impact on particle growth and hence on the particle size distribution. Synthesis of gold nanoparticles from HAuCl4 with rapid reduction by NaBH4 serves as a model system. Rapid reduction yields gold nuclei, which grow by agglomeration, and it is controlled by the interaction of the nuclei with local flow. Thus, the difference in the physical properties of the two phases and the inlet flow rates ultimately control the particle growth. Hence, a careful choice of continuous and dispersed phases is necessary to control the nanoparticle size and size distribution.

Gas-liquid flow and mass transfer in an advanced-flow reactor - Nieves-Remacha, Maria Jose; Kulkarni, Amol A.; Jensen, Klavs F. (Industrial & Engineering Chemistry Research, 2013)
Hydrodynamics and mass transfer of gas-liquid flow are explored under ambient conditions in an Advanced-Flow Reactor (AFR), an emerging commercial system designed for continuous manufacture. Carbon dioxide/water is the model system used in this study for a range of flow rates for gas and liquid of 5.6-103 mL/min and 10-80 mL/min, respectively. Bubble size distribution, gas holdup, specific interfacial area, pressure drop, and mass transfer coefficients are determined from flow visualization experiments and compared with conventional gas-liquid contactors. These variables are mainly influenced by the inlet flow rates and inlet composition. Average bubble sizes ((d) over bar (B)) of 0.9-3.8 mm, gas holdup (epsilon(G)) of 0.04-0.68, specific interfacial areas ((a) under bar) of 160-1300 m(2)/m(3), and overall mass transfer coefficients (k(L)(a) under bar) of 0.2-3 s(-1) were obtained for the vertical orientation of the AFR. Although effect of gravity is present for this system, no significant effect on the hydrodynamic properties was observed. The measured pressure drop for vertical orientation (3.6-53.4 kPa) was used to estimate power consumption, which is used as a metric to compare mass transfer efficiency among different gas-liquid contactors. A power law relationship was obtained for the overall mass transfer coefficients in terms of power input and gas holdup, given by kL (a) under bar = 0.101P(w)(0.443)epsilon(0.459)(G). The design of the AFR with a series of heart-shaped confined sections with obstacles enhances continuous breakup and coalescence of bubbles providing interfacial areas and mass transfer coefficients 1 order of magnitude larger than other gas-liquid contactors, such as bubble columns (50-600 m(2)/m(3); 0.005-0.24 s(-1)) and spray columns (75-170 m(2)/m(3); 0.015-0.022 s(-1)), and 1 order of magnitude smaller than gas-liquid microchannels (3400-9000 m(2)/m(3); 0.3-21 s(-1)) or falling film reactors (20,000 m(2)/m(3)).

OpenFOAM computational fluid dynamic simulations of single-phase flows in an advanced-flow reactor - Nieves-Remacha, Maria Jose; Kukarni, Amok A.; Jensen, Klavs F. (Industrial & Engineering Chemistry Research, 2015)
Computational fluid dynamic (CFD) simulations are carried out for single-Phase flow in an, advanced-flow reactor (AFR) using the open source software OpenFOAM. Excellent agreement of Simulations with experimental pressure drop and residence time distribution (RTD) is obtained. Streamlines, stagnant zones, Velocity profiles, and pressure fields are,obtained at different flow rates ranging from 5 to 100 mL/min. A change in the flow behavior with the presence of recirculation zones is observed with a 40 mL/min flow rate. The extent of the recirculation zones increases with increasing flow rate from 40 to 60 mL/min and is limited further by the presence of a second cylindrical post inside the heart cell, remaining almost constant in the flow rate range of 60-100 mL/min. The RTD is also determined for all flow rates, and a. comparison between different reactor designs (two-post, single-post, and low-flow-reactor-like single-post) is presented. The APR Shows a plug-flow behavior with a small degree of dispersion, which broadens the RTD. Symmetric RTD curves are obtained for the single-post designs, whereas the Gen 1 APR design experiences asymmetry in the RTD at flow rates in the range between 20 and 60 mL/min.